Pengaruh Knowledge Management Practices terhadap Organizational Performance - Anggraynie, Ratih Dwi (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2024)
This study aims to explore the relationship between employee performance and knowledge management practices (KMP) within an organization. The analysis was conducted on data from 20 respondents using statistical methods such as Pearson correlation and linear regression. The results show a highly significant correlation between employee performance and KMP, with a correlation value of 0.944 at a 0.01 significance level. Regression analysis indicates that employee performance significantly influences KMP, with a regression coefficient of 0.656, and the model explains 89% of the variation in KMP. This suggests that improving employee performance not only enhances individual productivity but also substantially strengthens the organization's capacity to manage and utilize knowledge. The practical implications of these findings emphasize the importance of integrating strategies for improving employee performance with knowledge management practices. Organizations are advised to focus on developing training programs, evaluations, and feedback mechanisms aimed at enhancing performance and strengthening knowledge management practices. Investing in support systems and a culture that encourages knowledge sharing will result in sustainable performance improvements and increase the overall effectiveness of knowledge management within the organization. With this holistic approach, organizations can achieve significant competitive advantages in an increasingly dynamic and complex business environment.